FEMA GRAS assessment of natural flavor complexes: Citrus-derived flavoring ingredients. (February 2019) - Cohen, Samuel M.; Eisenbrand, Gerhard; Fukushima, Shoji; Gooderham, Nigel J.; Guengerich, F. Peter; Hecht, Stephen S.; Rietjens, Ivonne M.C.M.; Bastaki, Maria; Davidsen, Jeanne M.; Harman, Christie L.; McGowen, Margaret; Taylor, Sean V.
Abstract: In 2015, the Expert Panel of the Flavor and Extract Manufacturers Association (FEMA) initiated a re-evaluation of the safety of over 250 natural flavor complexes (NFCs) used as flavoring ingredients. This publication is the first in a series and summarizes the evaluation of 54 Citrus -derived NFCs using the procedure outlined in Smith et al. (2005) and updated in Cohen et al. (2018) to evaluate the safety of naturally-occurring mixtures for their intended use as flavoring ingredients. The procedure relies on a complete chemical characterization of each NFC intended for commerce and organization of each NFC's chemical constituents into well-defined congeneric groups. The safety of the NFC is evaluated using the well-established and conservative threshold of toxicological concern (TTC) concept in addition to data on absorption, metabolism and toxicology of members of the congeneric groups and the NFC under evaluation. As a result of the application of the procedure, 54 natural flavor complexes derived from botanicals of the Citrus genus were affirmed as generally recognized as safe (GRAS) under their conditions of intended use as flavoring ingredients based on an evaluation of each NFC and the constituents and congeneric groups therein. Highlights: Safety evaluation of Citrus -derived flavoring ingredients. Evaluation used procedure for naturals developed by the FEMA Expert Panel. FEMA GRAS status determined/affirmed for 54 Citrus -derived natural flavor complexes.